Agility, speed, and coordination differences between national and international handball referees - Šegota, D.; Swalgin, K. L.; Belcic, I. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
The main aim of this paper is to determine differences in certain motor tests between national and international referees. Partial aim was to determine levels of motor abilities and to rank referees according to z-values in motor abilities which have an influence on quality of refereeing in handball. The study investigated a sample of 32 top-level handball referees in Croatia divided into national and international referees. The results showed significant differences in all variables (between p<0.01 and 0.02) between national and international referees. Calculated z-values for certain motor abilities that are important for success in match officiating revealed that international referees are ranked higher than national referees. Statistical power is moderate, but it could be concluded that national and international referees in this study have statistically significant differences in all variables assessing motor abilities space (agility, speed and coordination). Although other variables have an influence on quality of refereeing, it can be concluded when referees reach interval of z-values, they will also have their quality of refereeing at the level which is needed to officiate matches at the highest levels of competitions with success.